Apical hard‐tissue deposition in adult teeth of monkeys with use of calcium hydroxide - Holland, R.; Souza, V.; Nery, M. J.; Bernabe, P. F.E.; Mello, W.; Filho, J. A. Otoboni (Wiley, 1980)
Abstract— The periapical tissues of adult teeth of monkeys were examined histologically after root canal treatment with calcium hydroxide. Healing, as evidenced by complete apical closure with a hard tissue bridge and an inflammation‐free periodontal ligament, occurred more frequently where canals were instrumented 1 mm short of the apex. Overinstrumented canals exhibited a significantly decreased incidence of apical closure. 1980 Australian Dental Association